2011
DOI: 10.1038/ajg.2011.164
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of, and Risk Factors for, Chronic Idiopathic Constipation in the Community: Systematic Review and Meta-analysis

Abstract: Pooled prevalence of CIC in the community was 14%, and of similar magnitude in most geographical regions. Rates were higher in women, older individuals, and those of lower socioeconomic status. Presence of IBS was strongly associated with CIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
528
7
41

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 708 publications
(641 citation statements)
references
References 56 publications
32
528
7
41
Order By: Relevance
“…7 Similar results were reported in other studies where the prevalence of FC varied from 2.6% to 30.7% of the general population. 8,15,16 The dichotomy in the data is due to the reason that in our study, the subtypes of constipation in already diagnosed constipated patients has been studied, unlike reported literature which has assessed the prevalence of constipation subtypes in the community at large.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…7 Similar results were reported in other studies where the prevalence of FC varied from 2.6% to 30.7% of the general population. 8,15,16 The dichotomy in the data is due to the reason that in our study, the subtypes of constipation in already diagnosed constipated patients has been studied, unlike reported literature which has assessed the prevalence of constipation subtypes in the community at large.…”
Section: Discussionsupporting
confidence: 80%
“…Hence, systematic evaluations are better rather than relying on patient to volunteer information related to their specific symptoms for better management of these patients. 2,7,8 Little is known about the epidemiology and clinical subtypes of constipation in the general Indian constipated population. Hence, the present study was conducted to evaluate the prevalence of FC and IBS-C in Indian constipated patients along with assessment of their demographic, socioeconomic, lifestyle and dietary habits, usage of constipation-related medications and comorbid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Constipation appears to be more common among women; [4,10,11] in one Australian study, [12] the prevalence of constipation was 24% in middle-aged women. However, the higher prevalence in women has been questioned by McCrea et al [11] that suggested that the higher prevalence in women could be due to women being more prone to report symptoms and to participate in research.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of the prevalence of constipation range from 10% to 15% in North America. 1 In the survey administered to Asians, the prevalence of chronic constipation was reported as 15-23% of female respondents and 11% of male respondents 2,3 and the prevalence of self-reported constipation was 16.5% in the general population and 9.2% of 'functional constipation' according to the Rome II criteria. 4 Constipation substantially affects the quality of life in that 70% of respondents feel its disruption to their day-to-day activities.…”
Section: Introductionmentioning
confidence: 99%